Rethinking urban riparian ecosystems as a frontline strategy to counter climate change: mapping 60 years of carbon sequestration evolution in Padua, Italy - Peroni, Francesca; Codato, Daniele; Buscemi, Luca; Cibrario, Marco; Pappalardo, Salvatore Eugenio; De Marchi, Massimo (Frontiers in Climate, 2023)
Nature-Based Solutions are considered essential measures to face climate change in cities. Riparian ecosystems are often undervalued as NBS even if they represent an “already plugged-in” ecosystem services providers. However, applied research on urban riparian ecosystems is scarce. To fill the gap, this study frames the role of these ecosystems as a frontline mitigation and adaptation strategy by (i) investigating how urban riparian ecosystems experienced a process of urbanization from World War II until today in Padua (Italy), ii) estimating how effective was carbon sequestration, iii) assessing how an afforestation process might contribute to mitigation scenarios. Land use/land cover changes are firstly mapped with high-resolution aerial images and, by using InVEST models, carbon sequestration is estimated. Results highlight that impervious surfaces notably increased along these ecosystems; hence, carbon sequestration was negative (- 928 Mg/C). Future scenario (2022-2050) indicates an increase of carbon stocks (+ 4,329.95 Mg/C), giving a contribution towards city carbon neutrality. Results suggest that, in the recent past, the urban management and policies did not provide a clear and well-defined planning of these areas. On the contrary, at present, urban riparian ecosystems might represent already existing multi-functional NBS to be restored and enhanced within cities for climate-resilient planning and for increasing life quality of city dwellers. Finally, our methodology provides a replicable spatial database for supporting of urban planning policies.